Use of electromagnetic, geoelectric and seismic tomography refraction geophysical methods to estimate the water content in the subsoil - Leucci, Giovanni (Italian journal of engineering geology and environment, 2005)
The interpretation of combined geophysical methods [Ground Penetrating Radar (GPR), Electrical Resistivity Tomography (ERT) and Seismic Refraction Tomography (SRT)] are proposed to assess the physical properties characterizing the near surface porous formations, and in particular way the volumetric water content. The search was carried out in semi-controlled situations. The variations of several geophysical parameters (the electromagnetic (EM) wave velocity, the seismic wave velocity and the electrical resistivity) were considered in the subsoil to estimate the fluctuations of the volumetric water content in the same subsoil. Is, in fact, known that the values of the geophysical parameters, that can be obtained from measures in surface, are influenced by the presence of water in the pore and in the fractures of the materials in the subsoil. The esteem of the variations of these parameters can be makes by measures repeated in the time (i.e. measures realized before and after water’s immission in the subsoil). This type of monitoring can allow the individualization of the principal paths of outflow of the water in the subsoil. The study conducted in this paper point out as the use of combined geophysical methods providing models of water outflow from the surface down to some meter deep.